2018
DOI: 10.1038/s41598-018-29989-0
|View full text |Cite
|
Sign up to set email alerts
|

Complete human mtDNA genome sequences from Vietnam and the phylogeography of Mainland Southeast Asia

Abstract: Vietnam is an important crossroads within Mainland Southeast Asia (MSEA) and a gateway to Island Southeast Asia, and as such exhibits high levels of ethnolinguistic diversity. However, comparatively few studies have been undertaken of the genetic diversity of Vietnamese populations. In order to gain comprehensive insights into MSEA mtDNA phylogeography, we sequenced 609 complete mtDNA genomes from individuals belonging to five language families (Austroasiatic, Tai-Kadai, Hmong-Mien, Sino-Tibetan and Austronesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 49 publications
1
33
0
2
Order By: Relevance
“…Additionally, pairwise F ST values were verified for Cham and Khmer (as Khmer Loeu had only eight samples) over all samples, showing a Weir and Cockerham mean F ST estimate of 0.0027702, confirming the high homogeneity between the two groups. The populations with the lowest F ST values compared to our 264 Cambodian samples were the 1,234 samples from Thailand and Laos (Kutanan et al 2017 10 , F ST = 0.0102) and the 609 Vietnamese samples (Duong et al 14 , F ST = 0.016).…”
Section: Resultsmentioning
confidence: 56%
See 3 more Smart Citations
“…Additionally, pairwise F ST values were verified for Cham and Khmer (as Khmer Loeu had only eight samples) over all samples, showing a Weir and Cockerham mean F ST estimate of 0.0027702, confirming the high homogeneity between the two groups. The populations with the lowest F ST values compared to our 264 Cambodian samples were the 1,234 samples from Thailand and Laos (Kutanan et al 2017 10 , F ST = 0.0102) and the 609 Vietnamese samples (Duong et al 14 , F ST = 0.016).…”
Section: Resultsmentioning
confidence: 56%
“…( B ) Schematic representation of data sets analysed, letters A–H representing publications with the colour denoting the completeness of the mtDNA sequences (yellow = complete, red = control region (CR) sequences). A = Summerer et al (327 CR, 44 full) 18 , B = Bodner et al 16 (214 CR), C = Zhang et al (1,054 CR, 98 full) 2 , D = Kutanan et al (1,234 full) 10 , E = Kutanan et al (560 full) 12 , F = Kutanan et al (415 full) 11 , H = Duong et al (609 full) 14 , G = 1000 Genome samples from Vietnam (KHV. 99 full).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past hundreds of years, the TK people gradually migrated southward, driven by various cultural, political, economic, environmental and other relevant factors, and became the majority inhabitants of Southeast Asia [8,13,14]. In light of the complex population history of TK-speaking groups and the important role played in the peopling of East and Southeast Asia, the analyses of genetic variations in TK-speaking populations have been conducted in several studies using different sets of autosomal [15][16][17], X-chromosomal [18,19], Y-chromosomal [20,21], mitochondrial [13,14,[21][22][23] and genome-wide [7,24] markers. Previous studies showed that the Proto-languages of TK and AN might be related [25], and TK people from Thailand are related to AN speakers based on mitogenome sequences [14].…”
Section: Introductionmentioning
confidence: 99%